Phone as a Pixel: Enabling Ad-hoc, Large-Scale Displays Using Mobile Devices - Schwarz, Julia; Klionsky, David; Harrison, Chris; Dietz, Paul; Wilson, Andy (CHI '12 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2012)
We present Phone as a Pixel: a scalable, synchronization-free, platform-independent system for creating large, ad-hoc displays from a collection of smaller devices. In contrast to most tiled-display systems, the only requirement for participation is for devices to have an internet connection and a web browser. Thus, most smartphones, tablets, laptops and similar devices can be used. Phone as a Pixel uses a color transition encoding scheme to identify and locate displays. This approach has several advantages: devices can be arbitrarily arranged (i.e., not in a grid) and infrastructure consists of a single conventional camera. Further, additional devices can join at any time without re-calibration. These are desirable properties to enable collective displays in contexts like sporting events, concerts and political rallies. In this paper we describe our system, show results from proof-of-concept setups, and quantify the performance of our approach on hundreds of displays